Chronic Limb Threatening Ischemia masquerading as Vitamin D deficiency; A case report - Sarah Afzal Kothari; Hadia Iftikhar; Iqra Anis (Saudi Journal of Emergency Medicine)
Introduction: Limb Ischemia is an uncommon but high risk emergency. It mostly presents as a painful limb in patients with peripheral arterial disease with risk factors such as hypertension, diabetes, smoking and chronic kidney disease. Timely diagnosis and intervention are crucial for reversal of ischemia. It can cause significant morbidity and mortality if left untreated due to the devastating complications. Case Presentation: We report a 42 year old healthy male who presented to the emergency department with acute pain in his left leg for 2 days. He had a history of intermittent bilateral lower limb pain and paresthesia for 2 years. Apart from well controlled Diabetes, he had no other significant medical history and reported no trauma or addictions. The patient was being managed as vitamin D deficiency by physicians at different levels of the health care system over the course of 2 years for muscular spasms and nutrient deficiency with analgesia and vitamin supplementation. Upon examination the left leg was pale, cold to touch with reduced sensation in the foot as compared to the right leg. Power of the distal left lower limb was 3 ⁄ 5. The right leg had intact sensory and motor function. No pulses were palpable in the bilateral lower limb up till the femoral artery. Findings were further confirmed via handheld Doppler ultrasound and the vascular team was emergently taken on board with the primary diagnosis of chronic limb threatening ischemia. A subsequent CT angiogram of bilateral lower limb with contrast showed complete thrombosis of the abdominal aorta below origin of renal arteries, extending from L2 vertebral level distally into the common femoral and superficial femoral arteries bilaterally along with complete attenuation on the left side of the anterior and posterior tibial, common peroneal and dorsalis pedis. The right side had similar findings with weak flow in the dorsalis pedis. The inferior mesenteric artery was also found to be occluded proximally. Patient was managed with an intravenous heparin infusion followed by urgent bilateral femoral embolectomy. Post operatively he developed pain and swelling in the lower limb for which an emergent keg leg fasciotomy was performed. Intraoperatively he was found to have extensive necrosis of anterior compartment of leg and tibialis posterior. It was followed by an extensive hospital stay secondary to sepsis and required prolonged rehabilitation and physiotherapy. Currently the patient is gradually regaining power and recovering well. Discussion: Extensive thrombosis in a young healthy male is an unusual occurrence which led to the delay in diagnosis causing significant morbidity and psychological stress to the patient. The pain that the patient had been describing for 2 years was in fact intermittent claudication. Peripheral arterial disease and its subsequent complication of chronic limb threatening ischemia (CTLI) has a dismal prognosis , significantly reducing quality of life of patients along with a substantial risk of amputation and even death. This case emphasizes the need for a detailed history and examination in young patients presenting with chronic pain, especially at the primary care level to prevent the debilitating consequences of this disease. [SJEMed 2024; 5(1.100): S70-S70]